2004
DOI: 10.1128/iai.72.8.4521-4527.2004
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Vaccination against Cutaneous Leishmaniasis with a Particulated Leishmanial Antigen or DNA Encoding LACK

Abstract: We have previously demonstrated that oral delivery of a disease-promoting particulated antigen of Leishmania amazonensis (LaAg) partially protects mice against cutaneous leishmaniasis. In the present work, we sought to optimize a mucosal vaccine by using the intranasal route for delivery of different antigen preparations, including (i) LaAg, (ii) soluble recombinant p36/LACK leishmanial antigen (LACK), and (iii) plasmid DNA encoding LACK (LACK DNA). BALB/c mice that received two intranasal doses of 10 g of LaA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 39 publications
3
50
1
1
Order By: Relevance
“…There are different examples of how intra-nasal vaccination has led to protective immune responses against other non-mucosal, penetrative pathogens, including Plasmodium and Leishmania (Arakawa et al 2003(Arakawa et al , 2005Hirunpetcharat et al 1998 ;Pinto et al 2004). In addition, intra-nasal immunization with Toxoplasma gondii TgSAG1 and non-toxic heatlabile enterotoxins protected mice against challenge infection against T. gondii (Bonenfant et al 2001), and recently Igarashi et al (2007) showed that intranasal immunization in Balb/c mice with recombinant TgROP2, TgGRA5 and TgGRA7 applied with cholera toxin induced partial protection against tissue cyst formation after oral infection with Toxoplasma tissue cysts.…”
Section: Discussionmentioning
confidence: 99%
“…There are different examples of how intra-nasal vaccination has led to protective immune responses against other non-mucosal, penetrative pathogens, including Plasmodium and Leishmania (Arakawa et al 2003(Arakawa et al , 2005Hirunpetcharat et al 1998 ;Pinto et al 2004). In addition, intra-nasal immunization with Toxoplasma gondii TgSAG1 and non-toxic heatlabile enterotoxins protected mice against challenge infection against T. gondii (Bonenfant et al 2001), and recently Igarashi et al (2007) showed that intranasal immunization in Balb/c mice with recombinant TgROP2, TgGRA5 and TgGRA7 applied with cholera toxin induced partial protection against tissue cyst formation after oral infection with Toxoplasma tissue cysts.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that L. amazonensis parasites take advantage of the host IFN-γ response for their intracellular survival. However, in other circumstances such as following protective mucosal vaccination with parasite antigens, the systemic production of IFN-γ may be effective (Pinto et al 2004, Pinheiro et al 2006. Since the role of IFN-γ during L. amazonensis infection is controversial, we evaluated the course of lesion growth induced by L. amazonensis in IFN-γ KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Several Leishmania proteins have been identified, and the most comprehensively studied antigens include glycoprotein 63 (gp63) (Xu et al 1995;Bhowmick et al 2008), glycoprotein 46 (gp46) or parasite surface antigen 2 (PSA-2) (McMahon-Pratt et al 1992, 1993, Leishmania homologue of receptors for activated C kinase (LACK) (Coelho et al 2003;Pinto et al 2004), and focused mannose ligand (FML) (Palatnik de Sousa et al 1994;). …”
Section: New Perspectives For Applications Of Proteoliposomesmentioning
confidence: 99%